L’INTERVENANT DOIT ÊTRE UN PROBLÈME POUR LES ENFANTS ! - CORTIAL, Cédric (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
The Intervenient Must be a Problem for the Children! This article attempts to find a theoretically and philosophically consistant foundation for the role of the facilitator of philosophy with children and draws conclusions about the type of activity that this facilitator must do. This requires a thetic implication on what makes us philosophize. We defend then that it is by the concept of problem that the philosophy appears, and that thus the facilitator must act by being an instantiation of this very concept.